Structural design and magnetic properties study on two nitronyl nitroxide radicals–MnII complexes with hetero chain or mononuclear tri-spin structures. (29th March 2015) - Zhou, Na; Wang, Ya-Li; Wang, Hai-Li; Li, Wen-Jiao; Guo, Zhilin; Ma, Yue; Li, Li-Cun; Wang, Qing-Lun; Cheng, Peng; Liao, Dai-Zhang
Graphical abstract: Modifying the nitroxide radicals by substituent groups helps to get one-dimensional Mn(hfac)2 -bridged [Rad–Mn(hfac)2 ]2 chain or mononuclear tri-spin Rad–Mn(II)–Rad compounds. Abstract: Two Mn(II) complexes based on two nitronyl nitroxide radicals with different substituent R groups have been synthesized, and characterized structurally and magnetically: [[Mn(hfac)2 ]3 (NITPyOMe)2 ] (1 ) (hfac = hexafluoroacetylacetonate, NITPyOMe = 2-(5′-(2″-methoxy)pyridyl)-4, 4, 5, 5-tetramethylimidazozoline-1-oxyl-3-oxide) and [[Mn(hfac)2 ]3 (NITPhOEt)2 ] (2 ) (NITPhOEt = 4′-ethoxyphenyl-4, 4, 5, 5- tetra-methylimidazoline-1-oxyl-3-oxide). The X-ray crystal structure analyses show that modifying the substituent R groups with a donor N atom helps to get the one-dimensional Mn(hfac)2 -bridged [Rad–Mn(hfac)2 ]2 chain complex1, while the large steric hindrance of the NITPhOEt radical induces complex2 to be a mononuclear tri-spin compound, in which the central Mn(II) ion is coordinated by two hfac and two NITPhOEt radicals. Variable temperature magnetic susceptibility studies reveal that there are antiferromagnetic interactions between the Mn(II) ions and the radical through the N–O group in both of the two complexes.